PENCATATAN PERKAWINAN BEDA AGAMA DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL PASCA PUTUSAN PENGADILAN NEGERI NOMOR 1139/Pdt.P/2018/PN.Jkt.Sel. - Muhammad Rizki Nurdin Sidauruk (2023)
This study aims to analyze the registration of interfaith marriages at the Population and Civil Registration Service after the District Court decision No. 1139/Pdt.P/2018/PN.Jkt. The research method used is a qualitative research method that produces descriptive data using a normative juridical approach in the form of legal behavior products that focus on obtaining information in the form of legal texts that are relevant to the research subject. The study shows that the judge's decision to accept the application for interfaith marriage is an attempt to fill the void in the law on interfaith marriages because Law Number 1 of 1974 concerning Marriage does not contain any provisions that state the prohibition of interfaith marriages, this is confirmed by the Supreme Court Decision Number 1400 K. /Pdt/1986 dated January 20, 1989 which stated that the religious differences of the prospective husband and wife were not a prohibition on marriage, while from the other side by considering the elucidation of Article 35 letter (a) of Law Number 23 of 2006 concerning Population Administration which stated that marriage What is stipulated by the court is marriages carried out between religious people, and also considering Article 28 B paragraph (1) of the 1945 Constitution it is emphasized that everyone has the right to form a family and continue offspring through legal marriage, where this provision is in line with Article 29 of the 1945 Constitution. about guaranteed by the independent State for every citizen to embrace their respective religions. As for the implementation of the registration of interfaith marriages, it can only be registered with the Population and Civil Registration Service after going through a decision of the local District Court. Thus, for interfaith couples who will carry out marriages, both prospective bride and groom should submit an application for an interfaith marriage permit to the local District Court so that the marriage can be registered at the local Population and Civil Registry Service and can be guaranteed by the State.